Compost Organic Materials' Suitability as a Living Place for Rhinoceros Beetle Larvae (Oryctes rhinoceros Linnaeus) in Oil Palm Area: Kesesuaian Bahan Organik Kompos sebagai Tempat Hidup Larva Kumbang Tanduk (Oryctes rhinoceros Linnaeus) pada Lahan Sawit - Fauzana, Hafiz; Rustam, Rusli; Salbiah, Desita; Aritonang, Putra (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2023)
Rhinoceros beetle (Oryctes rhinoceros) is the primary pest of oil palm (Elaeis guineensis Jacq.). Applying oil palm empty fruit bunches (OPEFB) and various other organic materials to cultivated land is assumed to support the growth of rhinoceros beetles. The study aimed to determine the suitability of organic matter as a place for rhinoceros beetle larvae to live. The research was carried out experimentally using a completely randomized design (RBD) with eight treatments and four replications. The treatment was in the form of OPEFB, rice husk, sawdust, OPEFB + rice husk, OPEFB + sawdust, OPEFB + rice husk + sawdust, and OPEFB + rice husk + sawdust without composting. The results showed that the growth of rhinoceros beetle larvae tended to be best on an organic material combination of OPEFB + rice husk + sawdust without being composted. Meanwhile, rice husk is the most unsuitable organic material for developing rhinoceros beetle larvae. Applying organic matter to palm land should be composted beforehand to reduce Rhinoceros beetle infestation.